Nanoparticle-Induced Complement Activation: Implications for Cancer Nanomedicine - La-Beck, Ninh M.; Islam, Md. Rakibul; Markiewski, Maciej M. (Frontiers in Immunology, 2021)
Nanoparticle-based anticancer medications were first approved for cancer treatment almost two decades ago. Patients benefit from these approaches because of the targeted-drug delivery and reduced toxicity, however, like other therapies, adverse reactions often limit their use. These reactions are linked to the interactions of nanoparticles with the immune system, including the activation of complement. This activation can cause well-characterized acute inflammatory reactions mediated by complement effectors. However, the long-term implications of chronic complement activation on the efficacy of drugs carried by nanoparticles remain obscured. The recent discovery of protumor roles of complement raises the possibility that nanoparticle-induced complement activation may actually reduce antitumor efficacy of drugs carried by nanoparticles. We discuss here the initial evidence supporting this notion. Better understanding of the complex interactions between nanoparticles, complement, and the tumor microenvironment appears to be critical for development of nanoparticle-based anticancer therapies that are safer and more efficacious.